(untitled) (Research, Society and Development, 2023)
This article aims to evaluate, through an integrative review, the effects of treatment in burn patients using Hyperbaric Oxygen Therapy (HBO). It is a complementary intervention related to the biophysical and biochemical effects of oxygen in promoting an increase in its availability to cells and tissues, helping in the healing potential of wounds. This study was carried out in order to expose data and evidence about this treatment, evaluating the healing time, adverse reactions, costs and effectiveness. Articles were collected in the PUBMED, LILACS and SCIELO databases, during the month of January 2023. Subsequently, a careful analysis of the selected material was carried out in order to gather the most relevant information concerning the proposed theme. This review concludes on the advantages of using Hyperbaric Oxygen Therapy (HBOT), on how aiding the healing process in the treatment of burned patients can reduce their morbidity, mortality and hospital costs.